The Effects of Delayed Cord Clamping on 12-Month Brain Myelin Content and Neurodevelopment: A Randomized Controlled Trial - Mercer, Judith S.; Erickson-Owens, Debra A.; Deoni, Sean C.L.; Dean III, Douglas C.; Tucker, Richard; Parker, Ashley B.; Joelson, Sarah; Mercer, Emily N.; Collins, Jennifer; Padbury, James F. (American Journal of Perinatology, 2020)
Objective This study aimed to determine if delayed cord clamping (DCC) affected brain myelin water volume fraction (VFm) and neurodevelopment in term infants.Study Design This was a single-blinded randomized controlled trial of healthy pregnant women with term singleton fetuses randomized at birth to either immediate cord clamping (ICC) (≤ 20 seconds) or DCC (≥ 5 minutes). Follow-up at 12 months of age consisted of blood work for serum iron indices and lead levels, a nonsedated magnetic resonance imaging (MRI), followed within the week by neurodevelopmental testing.Results At birth, 73 women were randomized into one of two groups: ICC (the usual practice) or DCC (the intervention). At 12 months, among 58 active participants, 41 (80%) had usable MRIs. There were no differences between the two groups on maternal or infant demographic variables. At 12 months, infants who had DCC had increased white matter brain growth in regions localized within the right and left internal capsules, the right parietal, occipital, and prefrontal cortex. Gender exerted no difference on any variables. Developmental testing (Mullen Scales of Early Learning, nonverbal, and verbal composite scores) was not significantly different between the two groups.Conclusion At 12 months of age, infants who received DCC had greater myelin content in important brain regions involved in motor function, visual/spatial, and sensory processing. A placental transfusion at birth appeared to increase myelin content in the early developing brain.Key Points
Keywords: umbilical cord; iron; placental transfusion; delayed cord clamping; myelin